2019
DOI: 10.1080/25785826.2019.1642727
|View full text |Cite
|
Sign up to set email alerts
|

Novel topical and systemic therapies in atopic dermatitis

Abstract: Atopic dermatitis (AD) is the most common inflammatory skin disease driven by both terminal keratinocyte differentiation defects and type 2 immune responses, and this condition causes psychological and social morbidity. Although patients with severe AD require systemic immunotherapy, conventional agents including ciclosporin could not be used for several years due to side effects such as nephrotoxicity, hypertension and long-term risks of malignancy. It is well known that dupilumab, which blocks receptor bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 86 publications
1
17
0
2
Order By: Relevance
“…We have shown that IL‐4/IL‐13 interferes with this process. This has been also shown in a recent study by Brauweiler et al 30 Given that recent studies have revealed that aberrant keratinocyte differentiation underlies the pathophysiology of AD, 28 , 29 the IL‐13–ΔNp63 axis would have an important role in the dysregulated keratinocyte phenotype in AD. We observed that IL‐13 stimulation for 24 h at any stage of differentiation (pre‐differentiated, differentiating, and differentiated stages) slightly upregulated the ΔNp63 gene expression level.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We have shown that IL‐4/IL‐13 interferes with this process. This has been also shown in a recent study by Brauweiler et al 30 Given that recent studies have revealed that aberrant keratinocyte differentiation underlies the pathophysiology of AD, 28 , 29 the IL‐13–ΔNp63 axis would have an important role in the dysregulated keratinocyte phenotype in AD. We observed that IL‐13 stimulation for 24 h at any stage of differentiation (pre‐differentiated, differentiating, and differentiated stages) slightly upregulated the ΔNp63 gene expression level.…”
Section: Discussionsupporting
confidence: 57%
“…A growing body of studies have demonstrated that abundant IL‐13, a representative cytokine constituting type 2 inflammatory environment, derived from ILC2 or Th2 plays a pivotal role in the pathogenesis of AD 27 . On the contrary, accumulating evidence has demonstrated disturbed keratinocyte differentiation in AD 28,29 . Therefore, we investigated how IL‐13 affects ΔNp63‐mediated keratinocyte differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many novel developments for the treatment of moderate-to-severe AD (e.g., biologics, such as dupilumab, and small molecules, including Janus kinase inhibitors and aryl hydrocarbon receptor-modifying agents) [97,98].…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Eine erste randomisierte, doppelblinde, placebokontrollierte Phase-1-Studie zeigte vielversprechende Ergebnisse [28]: 25 Patienten erhielten insgesamt 4 Infusionen mit MOR106 oder Placebo im Abstand von einer Woche, gefolgt von einer Nachbeobachtungsphase von 10 Wo-chen. Es zeigten sich signifikante Unterschiede zwischen den beiden Gruppen, 83 % der Patienten mit der Maximaldosis erreichten einen EASI-50 nach 4 Wochen [28]. Weitere Studien werden benötigt, um diese Ergebnisse zu bestätigen.…”
Section: Anti Il17c: Mor106unclassified